2023
DOI: 10.3390/biomedicines11061607
|View full text |Cite
|
Sign up to set email alerts
|

Periodic and Aperiodic EEG Features as Potential Markers of Developmental Dyslexia

Abstract: Developmental Dyslexia (DD) is a neurobiological condition affecting the ability to read fluently and/or accurately. Analyzing resting-state electroencephalographic (EEG) activity in DD may provide a deeper characterization of the underlying pathophysiology and possible biomarkers. So far, studies investigating resting-state activity in DD provided limited evidence and did not consider the aperiodic component of the power spectrum. In the present study, adults with (n = 26) and without DD (n = 31) underwent a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The only exception was the regional analysis for the offset, where results indicated against including the group factor in the model. These findings diverge from previous research on an Italian cohort, which reported decreased exponent and offset in the dyslexic group at rest, specifically within the parieto-occipital region, but not the frontal region (Turri et al, 2023). Despite our study involving twice the number of participants and utilizing a longer acquisition time, we observed no group differences, even in the same cluster of electrodes (refer to Supplementary Material).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The only exception was the regional analysis for the offset, where results indicated against including the group factor in the model. These findings diverge from previous research on an Italian cohort, which reported decreased exponent and offset in the dyslexic group at rest, specifically within the parieto-occipital region, but not the frontal region (Turri et al, 2023). Despite our study involving twice the number of participants and utilizing a longer acquisition time, we observed no group differences, even in the same cluster of electrodes (refer to Supplementary Material).…”
Section: Discussioncontrasting
confidence: 99%
“…The participants in both studies were of similar ages. The only methodological difference – EEG acquisition with eyes open in our study versus both eyes-open and eyes-closed in the work by Turri and colleagues (2023) – cannot fully account for the overall lack of group differences observed. The diverging study outcomes highlight the importance of considering potential inflation of effect sizes in studies with smaller samples.…”
Section: Discussionmentioning
confidence: 61%
“…EEG signals for each channel and rhythm were recorded with a wearable EEG device, namely the Emotiv EPOC+, following the calculation of the relative band power (RBP). The power and energy spectral analysis of EEG oscillations is a well-established method for the study of cognitive processes [107][108][109][110]. The methodology for data collection and analysis was described in detail in our previous study, where the contribution of EEG recordings to the audio-visual recognition of words was explored in university students with DD [78].…”
Section: Eeg Recordingsmentioning
confidence: 99%
“…A few studies reported alterations in beta oscillations as well as in other frequency bands in individuals with DD during linguistic tasks tapping into phonological, orthographic and semantic processing (Rippon, 2000;Klimesch et al, 2001;Spironelli et al, 2008), but also in auditory rhythmic tracking tasks (De Vos et al, 2017;Chang et al, 2021). Importantly, Turri et al (2023) reported lower resting-state beta power over parieto-occipital sites in adults with DD, and showed that beta power in these cortical sites was a predictor of reading accuracy in DD but not in typical readers.…”
Section: The Role Of Beta Oscillations In Reading Developmental Dysle...mentioning
confidence: 99%